The Effects Pandemic Covid-19 on Indonesia Foreign Trade - Nur Syamsiyah, Misfi laili Rohmi, Tiara Juliana Jaya, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
Indonesia is a developing country whose needs are exported from abroad. Therefore Indonesia needs foreign trade to fulfill goods that cannot be produced domestically or to distribute goods in which Indonesia has an absolute advantage in producing these goods. However, the policies are taken by the domestic government and Indonesia's foreign trading partner countries to limit the spread of the Covid-19 virus have an impact on the inflow of goods to and from abroad. Thus, this study intends to see how the Covid-19 pandemic has affected Indonesia's foreign trade by using the Paired Sample T-test, which observes conditions before and during/after a pandemic occurs. This study found that the Covid-19 pandemic had an impact on Indonesia's foreign trade from the aspect of oil and gas exports, imports of raw materials, and imports of Indonesian capital goods.